Dimensions of Empowerment in Women Participating in Grassroots Feminist Movements - Lee, Sophia; Matthews, Brian; Torres, Jennifer (Psychology of Woman Journal, 2024)
Objective: This study aimed to explore the multidimensional nature of empowerment as experienced by women engaged in grassroots feminist movements in the United States. Methods and Materials: A qualitative research design was employed, utilizing semi-structured interviews with 29 women actively involved in feminist grassroots organizing across various regions of the United States. Participants were selected through purposive sampling to ensure diversity in age, ethnicity, and activist experience. Data collection continued until theoretical saturation was achieved. Interviews were conducted virtually, transcribed verbatim, and analyzed using thematic analysis, supported by NVivo software. The analysis followed Braun and Clarke’s six-phase approach to identify key themes and subthemes reflecting participants’ lived experiences of empowerment within activist contexts. Findings: The analysis revealed five major dimensions of empowerment: personal empowerment, collective empowerment, sociopolitical agency, transformational learning, and identity reclamation. Each category comprised multiple subthemes, such as self-awareness, solidarity, political voice, critical consciousness, and cultural pride. Participants described how grassroots activism facilitated internal growth, strengthened interpersonal connections, and expanded their engagement in civic and political life. The data highlighted how empowerment was not a fixed state but an evolving, contextual process shaped by resistance, relational dynamics, and ongoing learning. Quotations from participants illustrated how even small acts, such as asserting boundaries or sharing personal stories, contributed to broader transformations in identity and agency. Conclusion: Women’s participation in grassroots feminist movements fosters a dynamic and multifaceted empowerment process that transcends traditional institutional metrics. These findings underscore the importance of recognizing emotional, relational, and symbolic dimensions of empowerment, as well as the sociopolitical mechanisms through which women reclaim agency and challenge systemic inequalities. Supporting grassroots feminist efforts requires attention to sustainability, intersectionality, and collective care to maintain their transformative potential.